2018
DOI: 10.1051/matecconf/201814503007
|View full text |Cite
|
Sign up to set email alerts
|

On the modified Reynolds equation for journal bearings in a case of non-Newtonian Rabinowitsch fluid model

Abstract: Abstract. In this paper, a theoretical analysis of hydrodynamic plain journal bearings with finite length at taking into account the effect of nonNewtonian lubricants is presented. Based upon the Rabinowitsch fluid model (cubic stress constitutive equation) and by integrating the continuity equation across the film, the nonlinear modified 2D Reynolds type equation is derived in details so that to study the dilatant and pseudoplastic nature of the lubricant in comparison with Newtonian fluid. A dimensionless eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 16 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Kumare [9] analyzed the effect of slip condition on the peristaltic flow of Rabinowitsch fluid in the non-uniform channel. Many other studies about using the Rabinowitsch fluid have been also reported [10][11][12][13][14][15]. The study of the effective magnetic field through a fluid in the channel has become an increasingly attractive research area [16,17].…”
Section: Hasen and Abdulhadimentioning
confidence: 99%
“…Kumare [9] analyzed the effect of slip condition on the peristaltic flow of Rabinowitsch fluid in the non-uniform channel. Many other studies about using the Rabinowitsch fluid have been also reported [10][11][12][13][14][15]. The study of the effective magnetic field through a fluid in the channel has become an increasingly attractive research area [16,17].…”
Section: Hasen and Abdulhadimentioning
confidence: 99%
“…It should be noted that in the literature review, many studies have been reported on elastohydrodynamic lubrication of journal bearings considering the rheological behavior of lubricants. Among these research studies, we can cite that of Javorova et al, 31 where the performances of finite bearings lubricated with dilatant and pseudo-plastic Rabinowitsch flow models are investigated under the elastic deformation of the bearing liner. They have reported that the joint influence of elastic deformation and lubricants rheology significantly affects the main bearing characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, journal bearings with rigid linear and different geometrical configurations and operating conditions are the most studied sliding bearings. We may cite the following study examples: infinitely long, 35 short 36 and finite-length width 37,38 plain and partial bearings, porous bearings, 39 hydrostatic, 40 hybrid, 41 and non-circular elliptical, 42 two-lobe 43 and conical 44 journal bearings, etc. It should be noted that in the literature review, many studies have been reported on elastohydrodynamic lubrication of journal bearings considering the rheological behavior of lubricants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Nowadays journal bearings are still used in many advanced applications such as turbomachinery, aircraft engines, machine tools and automotive applications. 2 The shaft supporting system is very important for the performance of industrial rotary machines. Hydrodynamic bearings are able to carry the load under severe conditions, providing stabilizing support for the rotating shaft when subjected to unexpected dynamic forces.…”
Section: Introductionmentioning
confidence: 99%